2019
DOI: 10.1111/sjoe.12310
|View full text |Cite
|
Sign up to set email alerts
|

The Magic of the Personal Touch: Field Experimental Evidence on Money and Appreciation as Gifts*

Abstract: In this paper, we use two field experiments in professional settings to explore the effort levels of individuals in response to gifts. We extend the literature by looking at non‐financial gifts that signal worker appreciation and gifts that combine financial and non‐financial elements with or without a personal touch. We find that while money and appreciation are individually effective, these only work well together when they are combined with a personal touch. This suggests that responses to gifts are sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…We assigned participants to the treatments by sessions. Kube et al (2012) and Bradler and Neckermann (2019) find an effect size of around 0.45 when testing the effects of monetary versus non-monetary incentives. We take the effect size in these studies as the basis for our power calculations.…”
Section: Fixed Payment Schemementioning
confidence: 99%
See 3 more Smart Citations
“…We assigned participants to the treatments by sessions. Kube et al (2012) and Bradler and Neckermann (2019) find an effect size of around 0.45 when testing the effects of monetary versus non-monetary incentives. We take the effect size in these studies as the basis for our power calculations.…”
Section: Fixed Payment Schemementioning
confidence: 99%
“…2 However, in terms of the physical appearance, they look more like gift cards as they do not have card number, cardholder name, chips, or the names of international payment networks, such as VISA or MasterCard on them. To the best of our knowledge, no prior studies compared the forms of monetary incentives, while there have been studies comparing monetary and non-monetary incentives (Heyman and Ariely [2004], Kube et al [2012], Bradler and Neckermann [2019]). Comparing the effect of different payment mediums, in addition to well-studied comparison of monetary versus nonmonetary payments, is necessary since it is more common to provide monetary incentives in different forms than providing non-monetary incentives in economics experiments and in labour market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used this giving behavior as a proxy of prosocial behavior, as prior research has indicated that the expression of gratitude communicates a prosocial state (Grant & Gino, 2010;Tsang, 2006), acknowledges a responsibility to others (Alspach, 2009), and is associated with prosocial behavior such as providing help to strangers (Bartlett & DeSteno, 2006;Lazarus & Lazarus, 1994;Nowak & Roch, 2007). Accordingly, the act of writing thank you cards (or giving other gifts that show gratitude) is a proxy of prosocial behavior (Bradler & Neckermann, 2019;Carson, Muir, Clark, Wakely, & Chander, 2012;Froh et al, 2014). To further magnify the prosocial benefit that participants could bestow by giving thanks, participants learned that each thank you card that they gave to a recipient would give the recipient an added chance of winning a financial prize.…”
Section: Study 6: the Impact Of Subjective Age On Prosocial Behavior In The Fieldmentioning
confidence: 99%